The Efficacy of 4 Liters of Clear Liquids for Small Bowel Preparation Prior to Video Capsule Endoscopy - Nicholas Placone; Runalia Bahar; Surinder Mann (Korean Society of Gastrointestinal Endoscopy, 2020)
Background/Aims Optimal small bowel (SB) preparation for video capsule endoscopy (VCE) is controversial. Our study aimed to support the use of a specified volume of 4 liters of clear liquids for bowel preparation for VCE. Methods A retrospective review of 284 patients who underwent SB preparation with 2 liters of polyethylene glycol (PEG) and 284 patients who had 4 liters of clear liquid preparation. We analyzed image quality, endoscopic findings, completion rate, and transit times. Results The 4-liter clear liquid group had significantly higher mean image quality scores when compared to the PEG group (2.908±0.77 to 2.669±0.64, p<0.0001), as well as more studies with adequate preparation (72% to 64%, p=0.0214). Although the PEG group had more endoscopic findings on VCE (40% to 23%, p<0.0001), there was a significant difference in the indications for the procedure between the groups. There was no difference in the capsule completion rate or SB transit time. Conclusions Our data demonstrate significantly higher mean image quality scores when using a specified volume of 4 liters of clear liquid compared to 2 liters of PEG. This study supports the growing evidence of the effectiveness of a 4-liter clear liquid SB preparation as opposed to PEG for VCE.